Diagnostic pitfalls in ovarian androgen-secreting (Leydig cell) tumours: case series. (3rd April 2019) - Fanta, M.; Fischerová, D.; Indrielle-Kelly, T.; Koliba, P.; Zdeňková, A.; Burgetová, A.; Vrbíková, J.
Abstract: Leydig cell tumours of the ovary are rare and represent a diagnostic challenge not only due to their sporadic incidence but also due to the seemingly normal imaging. We present three cases of pre- and postmenopausal women who were presented with severe clinical signs of hyperandogenism where modern imaging modalities (including computed tomography (CT), magnetic resonance imaging (MRI) and positron-emission tomography combined with computed tomography (PET–CT)) failed to identify the tumour. Two patients underwent non-expert ultrasound, CT and MRI examination with uniform conclusion that ovaries are of normal appearance. One of the two patients even had a PET–CT performed, which was inconclusive. Our case reports show the importance of examination by specialists with established skills in gynaecologic ultrasonography in the diagnosis of the Leydig cell tumours. The most useful diagnostic tool seems to be the combination of age (postmenopause), symptoms (onset of hirsutism and virilisation), high total testosterone plasma values and expert sonography. On ultrasound, these tumours are unilateral, usually small, solid intraovarian nodules of a slightly increased echogenicity in contrast to the surrounding ovarian tissue, delineated by abundant perfusion with an enhanced vascularity. The appropriate setting of the sensitive colour Doppler is crucial for the detection of intraovarian Leydig cell tumour. Impact statement: What is already known on this subject? A diagnosis of Leydig cell tumours is based on ultrasound performed by a trained examiner or by MRI. CT or PET/CT are not among the primary methods of choice. According to the results of imaging investigations surgical treatment is planned. Because these tumours are usually benign and have a good prognosis the unilateral salpingo-oophorectomy is a standard procedure. What do the results of this study add? Our case series show how difficult it can be to establish the diagnosis of Leydig cell tumours by imaging, including transvaginal ultrasound, the most frequently recommended diagnostic tool. We demonstrate in three cases how easily a small hyperechogenic tumour can be overseen or interchanged for a different gynaecological pathology if transvaginal scan is not performed by an experienced examiner trained in sonographic features of gynaecologic neoplasms. What are the implications of these findings for clinical practice and/or further research? This case series demonstrate how important it is to see the patient in the whole complexity with their medical history, proper clinical symptoms evaluation, laboratory test and not to rely solely just on sophisticated high-end investigations, such as the PET–CT, a CT and an MRI. It also emphasises the importance of specialists with established skills in gynaecologic ultrasonography. Further effort should be made to define the resources for the appropriate training of such sonographers.